2013
DOI: 10.1016/j.neuroscience.2013.03.050
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of VEGF and VEGF-derived peptide in peripheral neuropathies

Abstract: Besides its prominent role in angiogenesis, the vascular endothelial growth factor (VEGF) also exerts important protective effects on neurons. In particular, mice expressing reduced levels of VEGF suffer from late-onset motor neuron degeneration, whereas VEGF delivery significantly delays motor neuron death in ALS mouse models, at least partly through neuroprotective effects. Additionally, VEGF protects dorsal root ganglion (DRG) neurons against paclitaxel-induced neurotoxicity. Here, we demonstrate that VEGF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 38 publications
0
39
1
Order By: Relevance
“…VEGF-A xxx b is a potent neuroprotective factor for neurons including DRG [13], as is the alternatively spliced variant VEGF-A xxx a, in chemotherapeutic, diabetic and traumatic neuropathies [12,14]. VEGF-A xxx a and VEGF-A xxx b signal through different downstream pathways on VEGFR2 activation, although both isoform families can act through ERK1/2 to exert neuroprotective actions [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF-A xxx b is a potent neuroprotective factor for neurons including DRG [13], as is the alternatively spliced variant VEGF-A xxx a, in chemotherapeutic, diabetic and traumatic neuropathies [12,14]. VEGF-A xxx a and VEGF-A xxx b signal through different downstream pathways on VEGFR2 activation, although both isoform families can act through ERK1/2 to exert neuroprotective actions [13].…”
Section: Discussionmentioning
confidence: 99%
“…VEGF-A 165 a is the archetypal pro-angiogenic factor that also has neuroprotective capacity in experimental diabetes [12]. The products of the vegf-a gene consist of two isoform families; VEGF-A xxx a and VEGF-A xxx b (xxx relates to amino acid number), generated by alternative pre-mRNA splicing that differ only in their terminal six amino acid sequences.…”
Section: Introductionmentioning
confidence: 99%
“…A recent trial demonstrated the efficacy of duloxetine in 25 gynecological patients treated with paclitaxel, showing a beneficial effect on TIN in 14 patients (56%), and a good profile of tolerability, also in patients previously treated and with different comorbidities [68]. Zhu [76] In vitro Ethoxyquin Action as Hsp90 modulators, neuroprotective Verheyen [77] In vivo (mice)…”
Section: Duloxetinementioning
confidence: 99%
“…In vitro and in vivo experiments have shown a decreased expression of the stress-related gene activating transcription factor 3 (ATF3) when VEGF is administered. Overexpressing VEGF receptor 2 transgenic mice were characterized by neuroprotective effects mediated through VEGF receptor 2 [77].…”
Section: Vegfmentioning
confidence: 99%
“…Verheyen et al have suggested that targeting the pathogenetic pathways implicated in DPN by utilizing vascular endothelial growth factor (VEGF) and VEGF-derived peptides may be an option for future therapies [148]. However, a recent clinical trial of VEGF in DPN was stopped due to lack of efficacy [149].…”
Section: Upcoming Strategies For the Treatment Of Painful Neuropathymentioning
confidence: 99%